Rancang Bangun Sistem Informasi Penilaian Kinerja Menggunakan Metode Management by Objective Pada WanaArtha Life Surabaya - Henrira, Luis (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: Performance appraisal is very important because it can affect the performance of the company. Performance Assessment Process on Adisarana WanaArtha Life Insurance (WanaArtha) is based on the acquisition of each of the sales team will be managed by the admin to determine targets for each sales, so that the performance appraisal can be monitored. And monitoring each acquisition employees can’t handle it. Because so many transcation everyday, admin can make a mistake when admin input some data.WanaArtha be more vigilant in managing its employees, due to the costs incurred to pay the salary of each employee monthly is quite large, some of the criteria that have been set by the WanaArtha able to generate monitoring the performance of each employee. WanaArtha requires a performance appraisal system in the process of monitoring each acquisition employees, Management By Objective (MBO) can be used in the assessment of performance in WanaArtha because of the salary of each employee is different in each level. With the Performance Assessment Information System is able to produce a report and recommendations based on the acquisition appraisal of each employee according to the criteria desired.Management By Objective (MBO) can be used in the assessment of performance in WanaArtha because of the salary of each employee is different in each level. And MBO can controlling much data different. assessors and employees also accepted ratings are established at the outset.